Penggunaan Telegram Sebagai Media Komunikasi Dalam Pembelajaran Online - Fifit Fitriansyah; Aryadillah - (Universitas Bina Sarana Informatika, 2020)
Communication media are all means used to produce, reproduce, distribute or disseminate and convey information. Communication media plays an important role in people's lives. One of the communication media that is often used in learning is online media, such as whats app, email, classroom and telegram. The purpose of this research is to get a picture of the communication process in learning by utilizing telegraph communication media. The method used in this research is descriptive qualitative method. Online learning is a teaching and learning process that utilizes the internet and digital media in the delivery of material. As a means of communication media that support the learning process, the use of telegrams is a source of communication that makes it easy for students to obtain information through groups. Like face-to-face classes, in virtual classes (e-learning) must also be managed well in order to create a conducive class with the activeness and creativity of lecturers as well as students in them. Keywords: Communication Media, Telegram, Online Learning